The Impact of Ball Handling Practice on the SMPN 1 Labuhan Haji Basketball Team's Dribbling Skills - Azlan, Wawan Muhammad; Afrian, Herman; Daniyantara, Didik; Nopiana, Rina; Tamim, Muhammad Husni; Hariadi, Hariadi; Suryansah, Suryansah (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. of this study is to evaluate the effect of ball handling training on dribbling skills in the SMPN 1 Labuhan Haji basketball squad. Materials and Methods. This study employs a quantitative experimental method, namely a One Group Pretest Posttest Design. Data gathering methodologies and tools utilize assessments aimed at evaluating student learning outcomes. An tool of this nature comprises ball handling tasks designed to assess pupils' dribbling proficiency. Results. The evaluative analysis indicated that the mean pretest score was 63.73. After the execution of a ball handling training program, the posttest results revealed a significant enhancement, yielding an average score of 86.06. Thus, the posttest score exceeds the pretest score, signifying a significant enhancement in the dribbling abilities of the SMPN 1 Labuhan Haji basketball squad. Research findings This indicates that exercise ball handling in connection to dribbling proficiency substantially affects the SMPN 1 Labuhan Haji basketball team, as demonstrated by the hypothesis testing findings using the t-test, which produced a significant value of 0.000, signifying it is below 0.05. The findings demonstrate the rejection of H0 and the acceptance of Ha, indicating that ball handling training significantly influences the dribbling skills of the SMPN 1 Labuhan Haji basketball team. Conclusion. This is evidenced by statistical analyses that indicate significant disparities. This suggests that training concentrated on ball handling can markedly improve players' abilities in ball control and dribbling. This training has proven successful in improving basketball teams' dribbling performance on the court. It is recommended that more complex and dynamic ball handling training variations be adopted. Moreover, doing video analysis of matches and collaborating with skilled trainers can substantially improve the dribbling skills of the basketball players at SMPN 1 Labuhan Haji.